Strategi Komunikasi Pemasaran UMKM: (Studi Kasus di Desa Alaspandan, Kecamatan Pakuniran, Kabupaten Probolinggo) - Nirwana Esa Rafida; Pardianto, Pardianto (Jurnal Ilmu Komunikasi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving the local economy, but still face various challenges in marketing their products effectively. This study aims to identify and analyze the marketing communication strategies implemented by MSME actors in Alaspandan Village, Pakuniran District, Probolinggo Regency. The research method used is a qualitative approach with a case study technique. Data was obtained through observation, in-depth interviews with MSME actors, and documentation. The results of the study indicate that the marketing communication strategies are: 1). Combination and collaboration of marketing communication by utilizing social media. 2). Offline marketing communication by participating in events or exhibitions. 3). Introduction through events in villages. 4). Branding strategies and attractive product packaging.